Using Religious Studies Theory to Access the Sacred in Counseling. Issue 2 (7th October 2018) - Gilbride, Dennis; Shannonhouse, Laura; Kessler, Samuel J.
Abstract : This article explores the ideas of Mircea Eliade, the works of other classic religious studies scholarship, and traditional religious practices for insights and strategies that can be used in contemporary counseling settings. The ideas are not intended to be proscriptive or comprehensive, but rather are offered as a way to more explicitly and intentionally access the potential of the sacred (as it is understood in classic religious studies texts) in counseling work. The authors focus on 4 specific areas: sacred space, sacred time, rebirth/return, and initiation/rites of passage.